The role of synoptic waves in the formation and maintenance of the Western Hemisphere circulation pattern - Tan, X; Bao, M; Hartmann, DL; Ceppi, P (Journal of Climate, 2017)
Previous studies have demonstrated that the NAO, the leading mode of atmospheric low-frequency variability over the North Atlantic, could be linked to northeast Pacific climate variability via the downstream propagation of synoptic waves. In those studies, the NAO and the northeast Pacific climate variability are considered as two separate modes that explain the variance over the North Atlantic sector and the east Pacific–North American sector, respectively. A newly identified low-frequency atmospheric regime—the Western Hemisphere (WH) circulation pattern—provides a unique example of a mode of variability that accounts for variance over the whole North Atlantic–North American–North Pacific sector. The role of synoptic waves in the formation and maintenance of the WH pattern is investigated using the ECMWF reanalysis datasets. Persistent WH events are characterized by the propagation of quasi-stationary Rossby waves across the North Pacific–North American–North Atlantic regions and by associated storm-track anomalies. The eddy-induced low-frequency height anomalies maintain the anomalous low-frequency ridge over the Gulf of Alaska, which induces more equatorward propagation of synoptic waves on its downstream side. The eddy forcing favors the strengthening of the midlatitude jet and the deepening of the mid-to-high-latitude trough over the North Atlantic, whereas the deepening of the trough over eastern North America mostly arises from the quasi-stationary waves propagating from the North Pacific. A case study for the 2013/14 winter is examined to illustrate the downstream development of synoptic waves. The roles of synoptic waves in the formation and maintenance of the WH pattern and in linking the northeast Pacific ridge anomaly with the NAO are discussed.